Novel Macrolide-Specific ABC-Type Efflux Transporter in Escherichia coli - Kobayashi, Nobuyoshi (American Society for Microbiology, 2001)
In the Escherichia coli genome, five putative open reading frame (ORF) clusters, mdlAB, ybjYZ, yddA, yojHI, and yhiH, have been assumed to be possible genes for ABC drug efflux transporters (I. T. Paulsen, M. K. Sliwinski, and M. H. Saier, Jr., J. Mol. Biol. 277:573–592, 1998). We cloned all of these ORFs in multicopy plasmids and investigated the drug resistance of drug-supersensitive host cells lacking constitutive multidrug efflux transporter genes acrAB. Among them, only ybjYZ gave significant erythromycin resistance and significantly decreased the accumulation of [(14)C]erythromycin. Therefore, ybjYZ was renamed macAB (macrolide-specific ABC-type efflux carrier). Plasmids carrying both the macA and -B genes conferred resistance against macrolides composed of 14- and 15-membered lactones but no or weak resistance against 16-membered ones. Neither of the two genes produced resistance alone. The DNA sequence suggests that MacB is an integral membrane protein with four transmembrane segments and one nucleotide-binding domain, while MacA belongs to a membrane fusion protein (MFP) family with a signal-like sequence at its N terminus. The expression of the histidine-tagged proteins confirmed that MacB is an integral membrane protein and MacA is a peripheral membrane protein. In addition, MacAB required TolC for its function in a way similar to that of most of the MFP-dependent transporters in E. coli. MacB is thus a novel ABC-type macrolide efflux transporter which functions by cooperating with the MFP MacA and the multifunctional outer membrane channel TolC. This is the first case of an experimentally identified ABC antibiotic efflux transporter in gram-negative organisms.